Fair value and its impact on the behaviour of the investment decision maker - Al-Mashhadani, Iman Shihan Abbas; Al-Fatlawi, Ali Abdulhassan Abbas (Journal of Economic, Administrative and Legal Sciences, 2021)
The study is intended to investigate the impact of applying fair value, as represented in two dimensions: the relevance of fair value accounting, and the obstacles confronting fair value accounting on investment decision making, for which the hypotheses of the study has been confirmed. The problem focusses on the impact of ambiguous standards, accounting disclosures, and the lack of credibility and reliability of investment decision making. The study is also intended to determine the positive effects of applying the fair value in terms of achieving quality in profits and enabling investment decision making to take correct decisions. The study attempts to investigate the role of fair value in determining the actual value of the entity depending on the market value of bank assets so as to improve future expectations and compare with other banks that depend on fair value. A questionnaire has been distributed to a sample of 70 individuals working at commercial banks in Karbala, Iraq. of accounts and auditors and investment decision-makers. we used multiple regression and the backward method in our statistical analysis. The study asserts the necessity to have legislation related to fair value and that consolidates the concepts of fair value and the ways in which this can be measured in banks through additional training courses.